Analysis of publications on “public television” indexed in Web of Science (2001-2019) - Gutiérrez-González, Carlos; González Pardo, Rafael (Historia y Comunicación Social, 2021)
In this article, we analyze the scientific production on public television disclosed between 2001 and 2019 in the Web of Science databases, characterizing the metadata information, and identifying media studies, traditions of communication theories and methodologies with content analyses. 202 articles were found that correspond to 1% of total publications with the keyword “television”, this show the gap in public television studies. The results demonstrate a centralization of knowledge in Spain and United States. Regions as Latin America, Asia and Oceania have a low participation. Finally, scholars have been interested in the production processes analyzed from the sociocultural tradition.